TUGAS DAN WEWENANG DPRD DALAM PENGAWASAN PELAKSANAAN APBD DI KABUPATEN BEKASI JURNAL ILMIAH - Fajar Bayu Suseto , Untung Dwi Hananto *), Ratna Herawati (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
Monitoring functions Bekasi Regency Council is one of the three functions of the Council in addition to the legislation and budget functions. Monitoring functions more focused on the function of Parliament in monitoring local regulation and Budget (APBD). In performing this function, the Council collaborates with the regents in conducting the discussion. Approved or not a draft budget in the future is a decision of the Council it self. Duties and powers of Council in monitoring the implementation of the Bekasi Regency, regulated in Bekasi Council Regulation No. 1 of 2010 about Bekasi Regency Council rule’s in controlling the budget is not only limited to the aspects ofthe use of funds, but also on the income and revenue. And monitoring performed by Council not only to the Council budget, but also the implementation of local regulation and decree. From the implementation of the monitoring function, it can be seen clearly the impact of the delivery of local government and regional development. All that perform supervisory duties is a commission by the commission fields each. The internal barriers about monitoring of management factors in Bekasi budget are education, experience, human resources regulations and programs, while the external resistance is change legislation, recruitment of political parties, public participation and the media.